Studies on obtaining Cu-CNT composites by continuous casting method (Metallurgy and Foundry Engineering, 2014)
The progress of civilization force that we look for new materials with higher exploitation properties that can be used in different types of installations and will allow to increase their technological potential. One of the research trends is concentrated on the search of new materials with the above standard electrical conductivity, mechanical and rheological properties, higher thermal resistance and technological properties, all in comparison to pure copper. One of the ideas of such material is composite produced from copper and high quality carbon materials (CNT’s or graphene). Regarding to the above, presented paper refers to the research results concentrated on the metallurgical synthesis of Cu-CNT’s materials obtained with the use of the continuous casting method. Within this paper research works over the synthesis method and obtained material characterization, for electrical, mechanical and structural properties (for both as cast and after cold drawing tempers) are shown.